Extracorporeal Ultrasound-Guided High Intensity Focused Ultrasound: Implications from the Present Clinical Trials - Tinghe Yu; Xiao Fu (The Scientific World Journal)
Extracorporeal ultrasound-guided high intensity focused ultrasound (HIFU) has been clinically used for 15 years, and over 36000 cases have been reported. However, there yet lacked a consensus in the clinical values, suggesting the necessity of checking clinical findings. Clinical trials were searched and data reevaluated. HIFU was hardly performed alone; almost all present anticancer means have been applied during an HIFU treatment, and a specific regimen varied between trials; there were heterogeneity and disagreement between trials. The complexity made it difficult to distinguish the effect of HIFU. Based upon evaluable data, the efficacy of HIFU was similar to that of radio frequency, chemoembolization, chemotherapy, radiotherapy, or hormone therapy; a combined therapy did not improve the efficacy. The survival rate of HIFU plus radiotherapy was lower than that of radical surgery in liver cancers. Adverse events had no downtrend in the past years. HIFU was not a standardized procedure where the intensity and insonation mode were modified constantly throughout a treatment, limiting an evaluation from the perspective of ultrasonics. These implied that HIFU should be applied as an alternative at most occasions. The present clinical trials had defects making against the understating of HIFU.